Chemotherapy-related side effects in childhood cancer in Hiwa Hospital Sulaimani city/Kurdistan region, Iraq - Ghazy Abdulkareem, Awayi; Salah Ramzi, Zhian; Ahmad Rashid, Jamal; Sulaiman Rahman, Heshu (Kurdistan Journal of Applied Research, 2019)
Cancer cells tend to grow fast, and chemo drugs kill fast-growing cells. However, since such drugs move to almost all part of the body, they might have an influence on healthy cells which are normal and grow fast. If healthy cells are damaged, there will be several side effects. The side effects of chemotherapy in children are reported by cancer treatment teams; however, only little evidence is available on the routine clinical care. The present study aimed to assess chemotherapeutic side effects in children with cancer. A single chemo drug can treat cancer; however, in order to come up with better and quicker results, sometimes a number of drugs are used in a specific order or combination which is referred to as combination chemotherapy. More cancer cells can be killed using different drugs which have different working mechanisms. As a result of this method, the cancer will have more limited chances to become resistant to an of the chemo drugs. The present descriptive study consisted of 300 children who underwent chemotherapy, and interviews were carried out with them. The severity of side effects was calculated according to three grades: low, moderate, and high. The collected data was collected through direct interview with the child greater than 6 years old on side effects of chemotherapy on physical health. Chemotherapy affects the entire cell inside the body among children. The results demonstrated that chemotherapy commonly affects the gastrointestinal tract and musculoskeletal system.